Orality in the civil process as an evolution of the princi ples governing the process (2011)
Through the implementation of orality and work focused on solving its possible insufficiencies, we will have in Colombia a complete oral system that allows a true effectiveness of the administration of justice, since it is not about obtaining quick and independent processes of the result, In addition to justifying the change, it is necessary to seek justice in these litigation, and the best way to do this is by bringing immediacy to the entire process as a guarantee of effective judicial protection and due process in civil matters.